How much could a microbicide's sexually transmitted infection efficacy contribute to reducing HIV risk and the level of condom use needed to lower risk? Model estimates. Issue 4 (10th February 2009) - Foss, A M; Vickerman, P T; Alary, M; Watts, C H
Abstract : Objective: This study explores the potential contribution of a microbicide's sexually transmitted infection (STI) efficacy in reducing a female sex worker's (FSW) risk of STI and HIV infection. The study then investigates whether the threshold for the reduction in condom use following microbicide introduction that can be tolerated without increasing HIV risk is affected by STI efficacy. Methods: A dynamic model describing the transmission of a bacterial STI between FSW and their clients was coupled with a static HIV model. The model uses data from Cotonou, Benin (1998–9), for illustration, to estimate the change in risk following the introduction of 50% HIV efficacious microbicides of different STI efficacies, used in 50% of sex acts when a condom is not used. The condom migration thresholds were estimated. The degree to which the findings are influenced by STI prevalence was explored. Results: For highly transmissible STI, there is a non-monotonic relationship between STI prevalence and microbicide impact on HIV with the relative reduction in HIV risk first increasing, due to the proportion of HIV risk attributable to the STI increasing, but then decreasing at high prevalences as the STI becomes harder to control. A less transmissible STI can still be impacted upon with a moderate/high STI efficacy microbicide even at high STI prevalences. This relationship is also reflected in the condom migration thresholds. Conclusions: A microbicide's STI efficacy may have a substantial impact on STI and HIV incidence among high-risk groups. The variation in the condom migration thresholds for different STI efficacies and STI prevalences may be difficult to measure accurately.